Didactic Visualization of Routing Problems - Margaretha Gansterer; Veronika Klug (MDPI AG, 2020)
The Traveling Salesman and Vehicle Routing Problems are integral parts of bachelor and master programs related to Operations Research/Management Science. This is due to their relevance in both practical applications and research. For students, it is essential to gain a deep understanding of the problems' inherent complexity. For this, several tools are available online. A systematic classification of both the Traveling Salesman Problem (TSP) and Vehicle Routing Problem (VRP) teaching material is provided and discussed. This classification takes target groups as well as learning objectives into account. Recommended choices depending on the teaching context are provided. A special focus lies on interactive visualizations, which seem to be most useful for supporting students in their solution-oriented competencies. We observe that didactic visualization tools for vehicle routing are scarce. This is surprising since, in practice, this problem is prevalent.